(3efGaY GdfHGJ hGdKeGQ hGdHbhd hGdahGcgs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdfNd gi Chd TLQI GSJbQJ Ydi hLg GdCQV hgj TLQI eHGQcI dG JhLO EdG HHdGO GdESdGe s
(3BNQgG (B:s
(3hfRdJ hLYdJ JdJaJ , afXQ GdCShGQ aEPG ai bYQ GdHFQ MjI ebJhdg , hYdi SfgG YbQH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH Gdhd (B- (3U (B183 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdGSJGP eMeO GdXGgQ GHf YGThQ (B- (3JhfS s
Keywords: (3GdWHs